Assessment of the three-dimensional flow field in the reactor pressure vessel in Hualong One nuclear power plants - Wei, Zonglan; Li, Songwei; Du, Sijia; Lu, Yazhe; Qiu, Zhifang (Frontiers in Nuclear Engineering, 2024)
The present study uses Computational Fluid Dynamics (CFD) method to investigate the threedimensional flow field under normal operation conditions in the reactor pressure vessel (RPV) in Hualong One Nuclear Power Plants (NPPs). With a particular focus on the flowrate distribution at the core inlet, the numerical framework is validated against the integral hydraulic experiment in a 1:4 scaled RPV of CNP1000, the prototype of Hualong One reactor. The simulation results of the normalized flowrate at the core inlet have reasonably good agreement with the measured data. Based on the experimental data, several ways of calibrating the CFD turbulence model coefficients are suggested by introducing the concepts of data assimilation and machine learning. The flow field in a realistic RPV of Hualong One is predicted using the validated numerical framework and it shows that the flowrate distribution at the core inlet is nearly homogeneous and the turbulent intensity is acceptably low for each fuel assembly, which can provide essential information for the reactor core thermal-hydraulic design and fuel assembly mechanical assessment.